Gauging the reception of Arab translators to the subtitles of taboo language in Hollywood movies - Yousef Sahari,; Wagdi Rashad Ali Bin-Hady (Studies in English Language and Education, 2025)
This investigation analyzes the appropriateness of Arabic equivalences of English taboo words according to the perceptions of the Arab translators. It also detects if there is a difference in the perceptions of the male and female translators in the subtitle of such taboo words according to the strategy used in the subtitling of taboos. The study asked translators to suggest their translations to the unacceptable sentences. A self-prepared scale of 16 sentences containing taboos was demonstrated with Arab translators. Sixty translators responded to the scale. The results showed that Arab translators moderately (M= 3.38) accept the translation of the taboo language. Results also showed that males (M=3.41) accept the rendering of taboos higher than females (M=3.31), however, the difference was not significant (Sig. =.831). Male translators prefer omission, cultural substation and reformation higher than female while female translators prefer direct translation over men. Findings also showed that translators provide some translations depending on using cultural substation to the taboo expression, followed by reformation. Omission was also preferred by some translations especially where direct subtitling was adopted. This study concludes that subtitling taboo expressions poses difficulties to translators which may not be easily worked on. This study recommends subtitling companies to balance between euphemising the offensive of taboo expressions and preserving the intended meaning provided.